Factors Influencing The Behaviour Of Traders In Waste Management At Nanggalo Market Padang City 2023 - Rizky Wahidyah; Awalia Gusti; Mahaza; Sri Lestari A; R. Firwandri Marza (Sustainable Applied Modification Evidence Community (SAMEC), 2024)
Waste is solid waste material from human activities at home, schools, shops, public places, markets and so on. One of the markets where there is still a lot of waste in Padang City is the Nanggalo Market in Padang City. Nanggalo Market is one of the traditional markets that sells the daily needs of the community in the market there are still many traders who litter and scatter, for this reason research was conducted at the Nanggalo Market. The purpose of this study was to determine the factors that influence the behaviour of traders in waste management in Nanggalo Market, Padang City in 2023. This research design is quantitative, conducted at Nanggalo Market, Padang City. The research was conducted from December 2022 to June 2023. The population was 408 traders in Nanggalo Market in Padang City with a sample of 80 traders, and the data analysis used was chi-square test statistics. The results showed that there was a significant relationship between knowledge and traders' behaviour in waste management (p<0.024), there was a significant relationship between attitudes and traders' behaviour in waste management (p<0.024), there was a significant relationship between facilities and traders' behaviour (p<0.004), there was a significant relationship between knowledge and traders' behaviour (p0.004), there is a significant relationship between government policy and traders' behaviour (p<0.000), and there is no significant relationship between the role of cleaning staff and traders' behaviour (p>0.182). It can be concluded that there are several factors that are related and some are not related to the behaviour of traders in waste management at Nanggalo Market, Padang City in 2023.